Housing in multiple occupation and studentification in Johannesburg - Gregory James J.; Rogerson Jayne M. (Bulletin of Geography. Socio-Economic Series, 2019)
Research concerning studentification is growing in importance. The supply of private student accommodation forms part of the wider urban process of studentification which documents changes in the social, economic and cultural fabric of cities. Although scholarly interest concerning the supply of private student accommodation has enjoyed sustained interest in the global North, only limited work is available surrounding the supply and demand for private student accommodation in global South urban centres. In South Africa there has been growing recognition of the impact of the studentification that has accompanied the massification of tertiary education in the post-apartheid period. Using interviews with key stakeholders, suppliers of student accommodation, as well as focus groups with students, this paper explores the supply of houses in multiple occupation and students’ perspectives on such properties in Johannesburg, South Africa. One distinctive influence upon the studentification process in South Africa is the impact of the national government funding system which was restructured in order to support the tertiary education of students from previously disadvantaged communities.